Synthesis of Zeolite X Molecular Sieve from Geothermal Solid Waste. (2019) - Widayat,; Hadiyanto,; Satriadi, Hantoro; Cahyono, Bambang; Astuti, Woro Indriani Setyo Tri; Febrianti, Pratika
Abstract: The objective of this research is to study effect of sodium hydroxide concentration on zeolite X preparation from geothermal solid waste. Synthesis of Zeolit X was conducted at temperature 150 °C, 5 hours for cystallization. Characterization was performed by XRD, SEM and BET. NaOH concentration affects significantly the type, morphology, pore volume and surface area of the resulted zeolite. Zeolite X was formed at the concentration of NaOH 3 M which had an octahedral crystal shape and having a specific surface area of 68.985 m 2 /gr and a pore volume of 0.109 cc/gr.